Racial and ethnic differences in reproductive knowledge and awareness among women in the United States - Jacqueline Y. Maher, M.D., M.A; Lubna Pal, M.B.B.S., M.S; Jessica L. Illuzzi, M.D., M.S; Natalie Achong, M.D., M.H.L; Lisbet S. Lundsberg, Ph.D., M.P.H (Elsevier, 2022)
Objective: To evaluate if knowledge and awareness of concepts and concerns pertaining to reproductive health and fertility vary by race/ethnicity among reproductive-aged women in the United States. Methods: A 2013 cross-sectional web-based survey assessed reproductive health-related knowledge, awareness, and perceptions of 1,000 women (18-40 years). Multivariable logistic regression analyses, adjusting for age, education, income, marital status, employment, region, and pregnancy history, examined the association between race/ethnicity and subfertility-related risk factor awareness; knowledge of factors that may affect pregnancy susceptibility; and future fertility-related concerns. Results: Knowledge and awareness related to reproductive wellness and fertility differed by race/ethnicity in US women. Compared with Caucasians, Hispanic women were less likely to be aware of smoking-related harm to fertility (odds ratio [OR], 0.57; 95% confidence interval [CI], 0.38-0.86); African American women were more aware of the implications of sexually transmitted infections on fertility (OR, 2.13; 95% CI, 1.15-3.94); and Asian women demonstrated greater awareness of a possible relationship between dysmenorrhea and subfertility (OR, 2.05; 95% CI, 1.09-3.86). Asian women consider fertility socially taboo to talk about and a private affair that is difficult to discuss (OR, 2.63; 95% CI, 1.32-5.29 and OR, 1.99; 95% CI, 1.05-3.75, respectively), were more concerned about their future fertility (OR, 2.36; 95% CI, 1.24-4.52), and more likely to perceive a need for future fertility treatment (OR, 2.36; 95% CI, 1.18-4.71). Conclusion: Among reproductive-aged women in the United States, knowledge, awareness, and perceptions relating to reproductive health vary by race/ethnicity. Our findings suggest race/ethnicity as potential modulators of population perceptions regarding reproductive health and infertility. Clinical Trial Registration Number: NIH ZIA# HD008985.